Bearing capacity of piles from cone penetration test data. - Eslami, Abolfazl. (University of Ottawa (Canada), 1997)
A direct CPTu method is proposed for determining the capacity of an axially loaded pile. The method employs all of the CPTu data with the cone point resistance, q$\rm\sb{c},$ as the primary measurement. The sleeve friction, f$\rm\sb{s},$ which is an imprecise measurement, is limited to use in combination with the effective cone resistance, q$\rm\sb{E}$ (cone point resistance adjusted to effective stress by deducting the measured pore pressure) to interpret the soil according to a classification chart, developed as a part of this dissertation. Both the pile unit toe and shaft resistances are functions of the CPTu effective cone resistance, with the toe and shaft correlation coefficients, C$\rm\sb{t}$ and C$\rm\sb{s},$ respectively. A database consisting of 192 case histories was compiled to calibrate and develop an improved CPT direct method, and to reference to the current CPT direct methods for pile capacity calculation. The case histories contain results of full-scale pile loading tests, soil characteristics, and CPT soundings which were performed close to the pile locations. The proposed method relates both the pile unit toe resistance and the unit shaft resistance to the effective cone point resistance, q$\rm\sb{E}.$ The hypothesis for the study was explored that both toe and shaft resistances are proportional to the effective cone resistance and can be determined by assigning a correlation factor to q$\rm\sb{E}.$ Twenty-four pile case histories have been compiled including static loading tests performed in uplift, or in push with separation of shaft and toe resistances at sites which comprise CPT soundings. These case histories are used to calibrate the two formulae for estimation of pile toe and shaft resistances from CPTu data. As a result of the calibration based on 24 pile case histories with separate measurement of pile toe and shaft capacities, for pile unit toe resistance, a simple mathematical rule is used to relate the cone resistance to the pile unit toe resistance in a one-to-one relationship. Five CPT direct methods currently used in North American practice have been investigated to reference the proposed method. The five CPT direct methods are: The Schmertmann method, the European Method, the French method, the Meyerhof method, and the Tumay method. The results of estimated pile capacity from the proposed method and the other methods were compared to the measured pile capacity for 142 case records compiled in the database. It was verified that the main factors that cause significant error in pile capacity estimation by the current methods are: smoothing the CPT data, development based on mechanical cone data, employing undrained shear strength, S$\rm\sb{u},$ imposing an upper limit to the pile unit toe and shaft resistances, not including all CPT measurement, considerable difference between the correlation factors for steel and concrete piles, considerable difference between the correlation factors for tension and compression piles, disregard of factors such as soil sensitivity, dilatancy effects, and effective stress. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.